2004
DOI: 10.1111/j.1464-410x.2004.05097.x
|View full text |Cite
|
Sign up to set email alerts
|

Prostatic capsule‐ and seminal‐sparing cystectomy for bladder carcinoma: initial results for selected patients

Abstract: OBJECTIVE To evaluate the oncological outcome and functional results of prostate‐sparing cystectomy (PSC), proposed for treating bladder cancer, used since 1999 in our institution in an attempt to preserve male sexuality and to increase continence after cystectomy. PATIENTS AND METHODS Between January 1999 and December 2001, 111 men were candidates for cystectomy; 42 were selected for a prostatic capsule‐ and seminal‐sparing cystectomy with orthotopic urinary diversion. All patients had clinically organ‐confin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(43 citation statements)
references
References 35 publications
1
38
0
4
Order By: Relevance
“…With regard to functional outcome, the overall postoperative potency preservation rates of the PSC series were 80%-94% and complete day-time and night-time urinary continence rates were close to 100% and 90%, respectively [29][30][31][32][33]. These rates are significantly superior to those described after standard cystoprostatectomy.…”
Section: Mainlan Chinamentioning
confidence: 71%
“…With regard to functional outcome, the overall postoperative potency preservation rates of the PSC series were 80%-94% and complete day-time and night-time urinary continence rates were close to 100% and 90%, respectively [29][30][31][32][33]. These rates are significantly superior to those described after standard cystoprostatectomy.…”
Section: Mainlan Chinamentioning
confidence: 71%
“…Thirty-five patients had a prostatic capsuleand seminal-sparing cystectomy. They were independently studied [10] and were excluded from this study. The mean age of the 294 remaining patients was 64.4 ± 9.6 years.…”
Section: Patient Populationmentioning
confidence: 99%
“…This is considerably lower than the rate for cystoprostatectomy series, and clearly indicates that prostatic involvement can be identified preoperatively (Table 2). 7,[13][14][15][16][17][18][19][20][21][22] Occult prostate cancer Coexistent prostate cancer exists in patients with invasive bladder cancer at approximately the same frequency as in normal men. The risk of prostate cancer incidence or mortality is not any higher in bladder cancer patients than in the normal population.…”
Section: Prostatic Involvement By Tccmentioning
confidence: 99%
“…In contrast, synchronous or metachronous prostate cancer in prostate-sparing series, where patients were screened for pre-existing prostate cancer, occurs in 2% to 4% (Table 2). 7,[13][14][15][16][17][18][19][20][21][22] Occasionally, even with this thorough screening, prostate cancer may develop. Vallancien and colleagues found that 3 of 100 men developed prostate cancer postoperatively.…”
Section: Prostatic Involvement By Tccmentioning
confidence: 99%